Perlindungan Hukum Terhadap Keamanan Data Pribadi Konsumen Teknologi Finansial dalam Transaksi Elektronik - A. A. Ngurah Deddy Hendra Kesuma; I Nyoman Putu Budiartha; Puru Ayu Sriasih Wesna (Jurnal Preferensi Hukum, 2021)
These days, the utilize of personal data is progressively gigantic in line with the current improvement of the digital industry, the publics submit their data to online applications such as Financial Technology and online trading as a necessity of being able to utilize these services. The formulations of the problem are 1J How is the Legal protection against the personal data of Financial Technology consumers? 2) What legal remedies can Financial Technology consumers take if the personal data is abused by the organizer? The results showed that personal data is information within the frame of identities, codes, symbols, letters, or numbers that demonstrate a person's individual identity. In the event that within the future there is a dispute and the consumer endures a misfortune, the casualty of personal data abuse can take legal action by way of deliberation and complaints to the Ministry of Communication and Information or OJK (non-litigation) and if it does 1101 resolve consumer disputes, they can record a gracious suit (litigation) 011 the premise of illegal acts IP M Hand askfor emolument